THE IMPACT OF BANK ACEH SYARIAH’S KUR FINANCING PROGRAM ON THE WELFARE OF MICRO, SMALL, AND MEDIUM ENTERPRISE ENTREPRENEURS IN ACEH BESAR - Mukahar, M. Agil; Syahputra, Hendra; Amanatillah, Dara (Journal of Sharia Economics, 2025)
Micro, small, and medium enterprises (MSMEs) are central to Indonesia’s economic development, contributing to gross domestic product (GDP), generating employment, and reducing unemployment. To strengthen this sector, the Indonesian government introduced the People’s Business Credit programme (Kredit Usaha Rakyat/KUR), which aims to provide financing access for MSMEs that face barriers in obtaining capital from formal financial institutions. Bank Aceh Syariah, as a key financial institution in Aceh, plays an active role in distributing KUR funds to local business actors. This study investigates the impact of KUR financing on the welfare of MSME actors in Aceh Besar. Using a qualitative case study approach, data were collected through in-depth interviews with MSME actors who received KUR financing, supported by direct observation of their business activities. The findings demonstrate that KUR financing has had a positive impact on the welfare of MSME actors by improving access to capital, enabling business expansion, increasing productivity, and broadening market networks. Furthermore, the programme has contributed to higher income levels and enhanced quality of life. However, challenges remain, particularly in financial management and marketing capacity. These results underscore the need for complementary support from financial institutions and government agencies through education and technical assistance, to ensure MSMEs can fully optimise the benefits of KUR financing.